2001
DOI: 10.14214/sf.608
|View full text |Cite
|
Sign up to set email alerts
|

Effect of accumulated duration of the light period on bud burst in Norway spruce (Picea abies) of varying ages

Abstract: One-year-old seedlings (two sowing times), two-year-old seedlings and 14-and 18-yearold cuttings of Norway spruce (Picea abies (L.) Karst.) were exposed to shortening photoperiod (initially 16 h), lengthening photoperiod (initially 6 h) and constant short photoperiod (6 h) treatments with uniform temperature conditions in growth chambers. The timing of bud burst was examined. In all plants, shortening photoperiod treatment seemed to promote bud burst compared with other treatments. This effect was clearest in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 27 publications
3
22
0
1
Order By: Relevance
“…Photoperiod thresholds estimated are lower than the ones proposed by Jolly et al (2005) and comparable to those found in many studies focused on the role of photoperiod in forest phenology for boreal species (Heide 1993;Rosenthal and Camm 1997;Partanen et al 1998;Worrall 1999;Partanen et al 2001;Keller and Körner 2003;Repo et al 2004;Wu et al 2004). The observed decrease in photoperiod thresholds can be explained by considering that thresholds values are optimized for a single species (i.e., Fig.…”
Section: Optimization Of Gsi Parameterssupporting
confidence: 84%
See 1 more Smart Citation
“…Photoperiod thresholds estimated are lower than the ones proposed by Jolly et al (2005) and comparable to those found in many studies focused on the role of photoperiod in forest phenology for boreal species (Heide 1993;Rosenthal and Camm 1997;Partanen et al 1998;Worrall 1999;Partanen et al 2001;Keller and Körner 2003;Repo et al 2004;Wu et al 2004). The observed decrease in photoperiod thresholds can be explained by considering that thresholds values are optimized for a single species (i.e., Fig.…”
Section: Optimization Of Gsi Parameterssupporting
confidence: 84%
“…In the temperate and boreal regions, temperature and photoperiod are considered the main factors influencing plant phenology Linderholm 2006), while at lower latitudes, in Mediterranean and tropical regions, rainfall and evapotranspiration act as important additional factors (Spano et al 1999;Peñuelas et al 2004). In alpine areas, temperature and photoperiod are the main ecological factors influencing phenological events: temperature affects many of the biochemical processes of plants (Levitt 1980;Öquist 1983) and photoperiod greatly influences autumn senescence and, more controversially, spring leaf development (Heide 1993;Worrall 1993;Partanen et al 1998Partanen et al , 2001Häkkinen et al 1998;Worrall 1999;Heide 2003). The accumulation of winter chilling also plays an important role in controlling bud-burst: the degradation of inhibiting hormones and the release of growth-promoting hormones during springtime also appear to be triggered by an accumulation of winter chilling (Schaber and Badeck 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Partanen et al (2001) hypothesised that the promoting effect of light intensity on budburst was caused by the absorbed radiation energy during clear, sunny days. The present results contest this hypothesis, as the observed advance in budburst timing in F. sylvatica, T. cordata and B. pubescens was too large to be attributed to increased bud temperature alone.…”
Section: Effect Of Light Intensitymentioning
confidence: 99%
“…The action of these environmental drivers is complex and changes along the transition from a dormant to a non-dormant state. In addition, it has been shown that photoperiod and temperature interact at various stages during dormancy induction, release and quiescence (Håbjørg 1972, Junttila 1980, Heide 1993, 2003, Myking & Heide 1995, Partanen et al 2001.…”
Section: Introductionmentioning
confidence: 99%